Complications during Pregnancy after Abdominal Burn Scars: A Review - Zosha J. van Gelder; Annabel Snoeks; Paul P.M. van Zuijlen; Ralph de Vries; Anouk Pijpe (MDPI AG, 2023)
Over the past decades, long-term sequelae of burns have gained increasing attention. Women of childbearing age, who sustained abdominal burns earlier in life, may have unmet information needs on scar-related complications they can expect during pregnancy. We performed a review of the literature to identify abdominal, foetal, and potential other complications during pregnancy in women with abdominal burn scars. PubMed, Embase, and Scopus were searched from inception to 1 July 2020 and updated once on 23 April 2021 (PROSPERO CRD42022187883). Main search terms included pregnancy, scar, burns, and abdominal. Studies on burns obtained during pregnancy have been excluded. Screening, data extraction and bias assessment were conducted by two investigators. We included 22 studies comprising 217 patients. The time between burn injury and first pregnancy varied between 7 and 32 years. Most of the women had normal pregnancies regarding delivery mode and duration of pregnancy. The most reported abdominal burn scar complications were an increased feeling of tightness, itch, pain, and scar breakdown. In some cases, scar release surgery was performed during or prior to pregnancy. Some cases of foetal complications were described. Complications during pregnancy after abdominal burn scars may be limited. More quantitative and qualitative research is needed to assess the maternal and foetal outcomes and complications. The results may be used to inform women and contribute to personalised obstetric management.